Perancangan Rumah Pengering Biji Kopi Menggunakan Plastik Ultra Violet (UV Solar Dryer) Dengan Mekanisme Konveksi Alamiah - Thomas J. Hudin; Verdy A. Koehuan; Nurhayati Nurhayati (Jurusan Teknik Mesin, Fakultas Sains dan Teknik, Universitas Nusa Cendana, 2021)
Now a days there are quite a lot of developed mechanical dryers (ERK) that use ultra violet plastic (Uv Solar Dryer) to replace the direct drying method when the weather is not supportive. UV Solar Dryer or also known as drying method using the greenhouse effect is a drying method that utilizes solar energy as the main source of heat energy for drying. The problem that will be focused in this research is to design a type of drying house (ERK) using ultra violet plastic with a natural convection mechanism which results in drying efficiency values of coffee beans ranging from 5-10%/hour. Based on the assumption that the initial moisture content of the coffee beans before drying is 60% and after going through the drying process for 16 hours, where per day the drying is carried out for 4 hours starting at 11.00 and ending at 15.00. The final moisture content of coffee beans obtained ranged from 11-12%. The drying rate obtained is 3.06% bk/hour (the level of water content evaporated for one hour of drying) where for each variation of air velocity the level of water content evaporated is the same. The highest drying efficiency obtained in this research is based on each variation of air velocity with an initial mass of 45.60 kg of material, namely at an air velocity of 0.1 m/s of 10.96%/hour occurred at 14.00, at an air velocity of 0.2 m/s at 11.53%/hour occurred at 14.00 and at air velocity of 0.3 m/s at 11.91%/hour occurred at 14.00.